Blockholdings and corporate governance in the EU banking sector - Matthias Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Ownership structures widely differ across the EU. While large blockholdings dominate in the banking sector in Continental Europe, ownership is widely dispersed in the United Kingdom. These differences have consequences for corporate governance in the EU banking sector. This paper analyzes the efficiency of shareholder control and hostile takeovers as corporate governance mechanisms in the EU banking sector against the background of the regulatory environment and differences in the ownership structure of banks. Particular attention is put on current trends in the ownership structure of banks (e. g. sovereign wealth funds). The paper is based on a new dataset on shareholdings in listed banks in the EU banking sector. The results indicate that EU regulations have not always improved corporate governance in the banking sector. While shareholder control has been improved by a better protection of minority shareholder rights, the efficiency of the takeover market has been reduced in Continental Europe.
Older version: http://hdl.handle.net/10419/27593
Keywords: G21; G34; G38; K29; 330; Banks; blockholdings; corporate governance; hostile takeovers; takeover directive; Bank; Eigentümerstruktur; Corporate Governance; Übernahme; Regulierung; EU-Staaten